Modelling Z→ττ processes in ATLAS with τ-embedded Z→μμ data - Aad, G. (2015)
This paper describes the concept, technical realisation and validation of a largely data-driven method to model events with Z → ττ decays. In Z → µµ events selected from proton–proton collision data recorded at √ s = 8 TeV with the ATLAS experiment at the LHC in 2012, the Z decay muons are replaced by τ leptons from simulated Z → ττ decays at the level of reconstructed tracks and calorimeter cells. The τ lepton kinematics are derived from the kinematics of the original muons. Thus, only the well-understood decays of the Z boson and τ leptons as well as the detector response to the τ decay products are obtained from simulation. All other aspects of the event, such as the Z boson and jet kinematics as well as effects from multiple interactions, are given by the actual data. This so-called τ-embedding method is particularly relevant for Higgs boson searches and analyses in ττ final states, where Z → ττ decays constitute a large irreducible background that cannot be obtained directly from data control samples. In this paper, the relevant concepts are discussed based on the implementation used in the ATLAS Standard Model H → ττ analysis of the full datataset recorded during 2011 and 2012